Die Bedeutung der Numismatik für das Studium des Alten Testaments - Oeming, Manfred (Congress volume Zurich 2022, 2026)
Although the iconography and epigraphy of coins is in no way inferior to that of seals, stamps or oil lamps, coins and their specific messages have received relatively little attention in Old Testament scholarship. This essay advocates paying much more attention to money as a hermeneutical factor in the interpretation of texts. It first offers a systematic exposition of the seven functions of money in trade, in military and administrative pay, in culture and art, in the formation of political identity, and in religion. Perhaps money changed people’s lives in much the same way as the introduction of a new basic material; one could therefore speak of the beginning of the “Coin Age” around 500BCE. In view of the insight that the final redaction of many Old Testament texts falls within this Coin Age, the contribution of numismatics should not be underestimated. A short review of thirteen possible, even probable influences of iconography of coins on the wording of Old Testament texts from Genesis to 2Chronicles and 2Maccabees should raise and strengthen an awareness of the importance of coins.
Gesehen am 20.01.2026